Platelets in Non-alcoholic Fatty Liver Disease - Dalbeni, Andrea; Castelli, Marco; Zoncapè, Mirko; Minuz, Pietro; Sacerdoti, David (Frontiers in Pharmacology, 2022)
Non alcoholic steatohepatitis (NASH) is the inflammatory reaction of the liver to excessive accumulation of lipids in the hepatocytes. NASH can progress to cirrhosis and hepatocellular carcinoma (HCC). Fatty liver is the hepatic manifestation of metabolic syndrome. A subclinical inflammatory state is present in patients with metabolic alterations like insulin resistance, type-2 diabetes, obesity, hyperlipidemia, and hypertension. Platelets participate in immune cells recruitment and cytokines-induced liver damage. It is hypothesized that lipid toxicity cause accumulation of platelets in the liver, platelet adhesion and activation, which primes the immunoinflammatory reaction and activation of stellate cells (HSC). Recent data suggest that antiplatelet drugs may interrupt this cascade and prevent/improve NASH and also some metabolic alterations. The pathophysiology of inflammatory liver disease and the implication of platelets are discussed in details.